In situ ruminal degradability of the dry matter of a supplement with the inclusion of white shrimp (Litopenaeus vannamei) waste .Technical note - Martínez, R.; Gutiérrez, D.; Guerra, J. E.; García López, R.; López, H. (Cuban Journal of Agricultural Science, 2019)
The objective of this study was to characterize the in situ ruminal degradability of the dry matter of a supplement with the inclusion of white shrimp waste (Litopenaeus vannamei) destined for dairy cows. A total of four bulls from Pardo Suizo breed were used with 700 ± 25 kg of LW, fistulated in rumen, fed with commercial concentrate (2 kg anim. day-1) and forage of Sudan grass (Sorghum sudanense), water and mineral salts ad libitum. The shrimp meal waste replaced (30 %) in the concentrate (70 %). A total of 84 dacron bags incubated in rumen in triplicate (72, 48, 24, 18, 8, 4, 0h) were used. The rumen degradability parameters reached values for the soluble fraction (a), insoluble fraction (b), for the potentially degradable (a+b), degradation rate (c) and effective degradability at different ruminal turnover rates (k = 0.02, 0.04) of 17.24 %, 66.63 %, 83.87 %, 2 % h, 64.20 % and 60.10 %, respectively. It is concluded that the parameters reached of dry matter degradation confirm the possibility of using the supplement with the inclusion of 30 % of shrimp waste in ruminant animals feeding, although the degradability of the rest of the nutrients should be characterized and carry out field tests with animals in production. Key words: rumiants, solubility, supplement